Involving Men in Reproductive and Fertility Issues : Insights from Punjab - Kamran, Iram; Khan, Mumraiz; Tasneem, Zeba (World Bank, Washington, DC, 2014)
Drawing on three sources, a 2013 qualitative study in four districts of Punjab province; a targeted analysis of the baseline and end line surveys of the Family Advancement for Life and Health (FALAH 2007-2012) project; and the Pakistan Demographic Health Survey (PDHS) of 1990-1991 and of 2006-2007, this study explores Pakistani (especially Punjabi) couples' dynamics during their decision processes on fertility intentions and practices, along with community perceptions of male-focused interventions as well as men's suggestions for future intervention strategies. It finds that men in Punjab seem now more concerned about their fertility intentions and practices due to the financial challenges of raising large families. This concern has not only increased spousal communication about family size and contraceptive use but has also encouraged Punjabi men to practice family planning. Most men now realize that either they or their wives should use family planning. It is the next step, however, of translating intention into practice, which is a challenge. Supply-side issues, including absence or paucity of family planning services as well as poor quality of services (including service providers' lack of capability to manage side effects) are the main factors hindering couples' adoption of family planning. Perceived or experienced side effects of contraceptive methods are other factors. Men's positive attitudes and their readiness to be involved in family planning programs suggest that the efforts of convincing men to use contraceptives have been effective and this it is now time for direct reproductive health interventions for men in Punjab. Yet heavy spending on media campaigns may not be as effective as interpersonal interventions. A focused effort to mobilize men through male-specific interventions is likely to increase the demand for contraceptives. These interventions have to be backed up by improved supply of contraceptives and availability of family planning services in accessible facilities.